Influence of a complex tratment on serum lipid profile and clinical course of ischemic heart disease in workers of mining industry. - V. I. Fesenko; V. A. Роtabashniy (Medičnì Perspektivi)
The aim of our study was to investigate the effectiveness of combined therapy with antiplatelet agent clopidogrel (Plagril®, “Dr. Reddy’sLaboratories Limited”, India), and lipid-lowering agent atorvastatin (Atocor®, “Dr. Reddy’s Laboratories Limited”, India) in the treatment of the miners with ischemic heart disease. A total of 30 miners have been under study. Complete physical examination, blood and urine tests, blood biochemistry, serum parameters of hemostasis, electrocardiogram, echocardiography, 24-hour ECG monitoring were performed. The treatment period was 3 months. It was established, that statin therapy with “Atocor” in combination with antiplatelet agent “Plagril” was well tolerated. The combination of medications significantly improves the clinical status of patients with coronary artery disease, along with effective correction of dyslipidemia without a negative impact on plasma hemostasis.